Система детекції людей у системах smart city - Гмиря, І. О. (ХНУРЕ, 2021)
The purpose of this article is to oreview the market of Smart City solutions and existing approaches to solving security issues in Smart City. The main goal of this article is to search for possible functionality for the detection system that is being created, which can be integrated as part of Smart City. The article also provides a short overview of possible functions, which describes the main tasks that the system solves. After considering the functionality, the architecture of the system being created, the selected development technologies, programming languages and frameworks are described.
Науковий керівник – к.т.н., доцент Чуприна А.С.
Keywords: система детекції людей; smart city